THE EFFECT OF DIRECT INSTRUCTION IN FORMULAIC SEQUENCES ON IELTS STUDENTS' SPEAKING PERFORMANCE - Gennadiy Goncharov (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2019)
In the light of previous research into the correlation between the acquisition of formulaic sequences and language learners' fluency gains, this study aims to investigate the extent to which an intensive course of direct instruction in preselected targeted formulaic sequences can improve IELTS students' oral fluency. In achieving this purpose, the researcher explores criteria for selecting formulaic sequences for intensive instruction as part of an IELTS speaking preparation course, and outlines principles for selecting and developing tasks and activities for the acquisition of formulaic sequences. The methodology for our intensive instruction course was quantitatively and qualitatively assessed using a group of five intermediate second language learners of English who had not received IELTS training before. A body of empirical data was gathered in pre- and post-course speaking tests conducted in full accordance with the IELTS format, with the test takers' performance being audio recorded. Recorded data were imported into Praat speech processing software to examine the temporal characteristics of the participants' speech. Analysis of the pre- and post-test recordings using a number of temporal measures revealed a significant increase in the number of targeted formulaic sequences used by the study participants after four weeks of intensive direct instruction. Analysis of the empirical data collected suggests a beneficial effect of formulaic sequence acquisition on both IELTS students' speaking performance and on their overall Speaking scores. The findings obtained are used to hypothesise to what extent formulaic sequences acquired through the course of direct instruction can influence test-takers' IELTS Speaking scores.